PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL MELALUI LEMBAGA ARBITRASE HUBUNGAN INDUSTRIAL - Bambang Yunarko (Perspektif, 2011)
Penyelesaian sengketa tidak diselesaikan di pengadilan, tetapi juga dapat diselesaikan melalui pengadilan umum dikenal sebagai penyelesaian sengketa alternatif, salah satunya adalah arbitrase. Hubungan industrial arbitrase untuk menyelesaikan perselisihan kepentingan dan hanya perselisihan antar serikat pekerja atau buruh di satu perusahaan. Undang-Undang Nomor 2 Tahun 2004 tentang Hubungan Industrial, khususnya arbitrase hubungan industrial Indonesia sesuai dengan prinsip lex specialis dan lex generali.The solution of dispute of shouldn’t be resolved in the court, in the court, but also can be resolved through but also can be resolved through the courts of commonly be known as alternative dispute solution, one of which is arbitration. Industrial relations arbitration to resolve disputes only the interest and disputes between union/union workers at one company. Act No. 2 of 2004 about industrial  relations, specifically arrange the particulars of arbitration of industrial relations in Indonesia accord with principle lex specialis derogat lex generali.